2015
DOI: 10.1016/j.molonc.2015.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Disulfiram (DSF) acts as a copper ionophore to induce copper‐dependent oxidative stress and mediate anti‐tumor efficacy in inflammatory breast cancer

Abstract: Cancer cells often have increased levels of reactive oxygen species (ROS); however, acquisition of redox adaptive mechanisms allows for evasion of ROS-mediated death. Inflammatory breast cancer (IBC) is a distinct, advanced BC subtype characterized by high rates of residual disease and recurrence despite advances in multimodality treatment. Using a cellular model of IBC, we identified an oxidative stress response (OSR) signature in surviving IBC cells after administration of an acute dose of an ROS inducer. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
121
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(139 citation statements)
references
References 46 publications
8
121
1
Order By: Relevance
“…We, and others, postulated that endogenous elevated intracellular copper predisposed the cancer cells to sensitivity, by possibly underpinning a heightened state of oxidative stress [8, 14, 17, 23]. However, we recently established that only a small subset of prostate cancer patients' harbour elevated intratumoral copper [26] and thus sought to clarify whether copper is indeed the critical, and targetable, factor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We, and others, postulated that endogenous elevated intracellular copper predisposed the cancer cells to sensitivity, by possibly underpinning a heightened state of oxidative stress [8, 14, 17, 23]. However, we recently established that only a small subset of prostate cancer patients' harbour elevated intratumoral copper [26] and thus sought to clarify whether copper is indeed the critical, and targetable, factor.…”
Section: Resultsmentioning
confidence: 99%
“…Raised intracellular ROS is a well-defined feature of human prostate cancer and clinical studies have unequivocally confirmed a role for oxidative stress in the development and progression of this disease [1922]. Therefore, it has been postulated that elevated endogenous copper may predispose prostate cancer cells to copper-ionophore sensitivity, by possibly underpinning a heightened state of oxidative stress [8, 14, 17, 23]. However, copper ions can exert toxicity through a myriad of mechanisms, including protein iron-sulfur cluster interference, proteasome inhibition and by displacing functional metals (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In matrix-on-top method, cells in single cell suspension are seeded on top of solidified matrix, followed by gentle agitation during incubation at 37°C. The cells spontaneously aggregate to form spheroids while remaining attached to the matrix (Allensworth et al , 2015; Ingeson-carlsson et al , 2015). In matrix embedded technique, cells suspended in liquefied matrix (chilled Matrigel) are dispensed onto the matrix pre-coated well and incubated at 37°C during which cells get embedded within the matrix upon gelation (Lee et al , 2007).…”
Section: Techniques For Generating Mctsmentioning
confidence: 99%
“…There are several methods for cell spheroid formation other than the microfluidic approach including magnetic levitation [34], 3D-bioprinting [35], hydrophobic surfaces [36], matrix-on-top [37], matrix-embedded [38], polymeric aqueous two-phase system [39], floating liquid marbles [40], multiwell plates [41], bioreactor flasks [42], liquid overlay [43] and HD techniques [36]. Some of these techniques such as HD and multiwell plates are laborious while some others like 3D-bioprinting and magnetic levitation are costly and still lack the standard protocols.…”
Section: Conventional Methods For Spheroid Formationmentioning
confidence: 99%